The Effect of Essential Oil on L4 Larvae of Culex Pipiens Mosquitoes - GRAIRIA NOUR EL HOUDA (My University, 2025)
This work aimed to study essential oils: Lavender oil, Eucalyptus oil, and a mixture of the two oils ‎‎(Lavender + Eucalyptus), and their effectiveness as natural insecticides against a mosquito species that is ‎widespread in our region, Culex Pipiens.‎ This study aimed to test the effect of essential oils with different concentrations of Eucalyptus oil ‎‎(Eucalyptus L.) (40, 100, 200 ul/l), Lavender oil (100, 200, 300 ul/l), and Lavender + Eucalyptus mixture (50, ‎‎100, 200 ul/l) on L4 larvae of Culex Pipiens mosquitoes.‎ The results in laboratory conditions showed that these oils have larvicidal efficacy. For Eucalyptus oil, ‎after 24 hours: CL₅₀ = 74.25 μl/l and CL₉₀ = 118.64 μl/l, while for Lavender oil, after 24 hours: ‎CL₅₀ = 143.72 μl/l and CL₉₀ = 179.49 μl/l, and for Lavender + Eucalyptus blend, after 24 hours: CL₅₀ ‎‎= 143.18 μl/l and CL₉₀ = 285.09 μl/l.‎ Our results indicate that these essential oils possess biocidal activity against mosquito larvae, ‎however, Lavender oil was found to be the most effective according to the results of the toxicity ‎test.‎ ------------------------------------------------------------------------------------------------------------------------------------- هدف هذا العمل إلى دراسة الزيوت الأساسية: زيت الخزامى، زيت الكاليتوس، ومزيج من الزيتين (الخزامى + الكاليتوس)، ‏ومعرفة فعاليتها كمبيدات حشرية طبيعية ضد أحد أنواع البعوض المنتشرة في منطقتنا، وهو‎Culex Pipiens.‎ تهدف هذه الدراسة إلى اختبار تأثير الزيوت الأساسية بتركيزات مختلفة من زيت الكاليتوس‎ (Eucalyptus L.) (40 µl ‎، 100، ‏‏200‏‎ )‎، زيت الخزامى‎ (ul/l 100‎، 200، 300‏‎)‎، ومزيج الخزامى + الكاليتوس‎ (ul/l 50‎، 100، 200‏‎) ‎على يرقات الطور ‏الرابع‎‎من بعوض‎Culex Pipiens.‎ أظهرت النتائج في ظروف مخبرية أن هذه الزيوت لها فعالية قاتلة لليرقات. بالنسبة لزيت الكاليتوس، بعد 24 ساعة: بلغت قيمة‎‎CL₅₀ = 74.25 ‎ميكرولتر/لتر وCL₉₀ = 118.64 ‎ µl ، أما بالنسبة لزيت الخزامى، بعد 24 ساعة‎: CL₅₀ = 143.72 ‎ µl/l وCL₉₀ = 179.49 ‎ µl/l ، وبالنسبة لمزيج الخزامى + الكاليتوس، بعد 24 ساعة‎: CL₅₀ = 143.18 ‎ µl/l وCL₉₀ = 285.09 ‎ µl/l ‎ تشير نتائجنا إلى أن هذه الزيوت الأساسية تمتلك فعالية كمبيدات حيوية ضد يرقات البعوض، ومع ذلك، فقد تبيّن أن زيت الخزامى ‏هو الأكثر فعالية وفقًا لنتائج إختبار السمية --------------------------------------------------------------------------------------------------------------------------------------- Ce travail nous permet d’étudier les huiles essentielles: Lavander, Eucalyptus et un mélange des ‎deux (Lavander + Eucalyptus),et de voir leur efficacité en tant qu’insecticides naturels contre une ‎espèce de moustique de notre région, CulexPipiens.‎ Cette étude vise à tester l’effet des huiles essentielles à différentes concentration des Huiles ‎d’Eucalyptus L (40,100,200 ul/l), Lavander (100,200,300 ul/l) et Lavande + Eucalyptus (50,100,200ul/l) à ‎l’égard des larves L4 de l’espèce de moustiques Culex Pipiens.‎ Les résultats dans les conditions du laboratoire ont montré que les larvicides intéressant vis-à-vis ‎les larves de Culex Pipiens.Chez l’huile d’Eucalyptus, après 24h: CL50=74,25 μl/l et CL90=118,64 μl/l, ‎chez Lavander, après 24h:CL50=143,72 µl/l et CL90=179,49 µl/l et lavander + Eucalyptus, après 24h ‎‎:CL50=143,18 μl/l et CL90=285,09 μl/l.‎ Nos résultats indiquent que ces huiles essentielles possèdent une efficacité en tant que biocides ‎contre les larves de moustiques, toutefois, l’huile de lavande s’est révélée la plus efficace, selon les ‎résultats du test de toxicité. ‎
Keywords: Insecticides; Eucalyptusoil; Lavender oil; Mosquitoes; Essential oils; Culex Pipiens. مبيدات حشرية، زيت الكاليتوس، زيت الخزامى، بعوض، زيوت أساسية، وبعوض Culex Pipien . Insecticides; huile de Eucalyptus; huile de Lavander; moustiques; huiles essentielles et Culex Pipiens